(untitled) (European Journal of Pedagogical Initiatives and Educational Practices, 2026)
This article analyzes the pedagogical opportunities for preparing future teachers for the creative use of modern pedagogical ideas. The theoretical and practical foundations of the use of innovative approaches, modern pedagogical technologies and creative methods in the educational process are highlighted. Also, important factors for developing professional competence of future teachers, forming creative thinking skills and preparing them for the effective use of modern ideas in pedagogical activity are identified. The results of the study serve to improve the quality of pedagogical education, strengthen the readiness of future teachers for innovative activities, and ensure the effectiveness of the educational process.